USE OF CORPORATE MANAGEMENT INFORMATION SYSTEMS PT. ADIRA DINAMIKA MULTI FINANCE COMPANY - Akbar, Fatawil; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study was to determine the application of management information systems at PT Adira Dinamika Multi Finance. This research is qualitative research with a descriptive analysis approach with literature studies in the form of library research and the company's official website in the form of library searches. The data collection method is taken from several references and does not require direct involvement in the field. A collection technique by paying attention, recording the desired information, then analyzing the data to organize data, present data and draw conclusions. Finally, the authors draw comprehensive conclusions about researching the literature and validating the data. the results of the study show that data input in the application of an online-based SIM has been implemented by PT Adira Dinamika Multi Finance s from the management, operational and technical aspects of financing services. The online-based SIM data process has been well implemented to provide convenience to customers and the public through the use of the Adiraku application, so that community data that has been entered can be immediately processed by PT Adira Dinamika Multi Finance. Output data in the implementation of an online-based SIM have been implemented to further improve work results in providing service.